2018
DOI: 10.1002/jbmr.3456
|View full text |Cite
|
Sign up to set email alerts
|

Low Muscle Strength and Mass Is Associated With the Accelerated Decline of Bone Microarchitecture at the Distal Radius in Older Men: the Prospective STRAMBO Study

Abstract: Low muscle mass and strength are associated with poor bone microarchitecture. We studied the association of muscle mass and strength with changes in bone microarchitecture of distal radius in 821 older men during an 8-year prospective follow-up. Bone microarchitecture was assessed by high resolution peripheral quantitative computed tomography (XtremeCT-1, Scanco) at baseline, then after 4 and 8 years. Relative appendicular lean mass of the upper limbs (RALM-u.l.) was calculated as DXA-measured lean mass of upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…In a more recent investigation over 8 years of follow‐up in the STRAMBO cohort, men in the lowest quartile of baseline grip strength had accelerated declines in total vBMD, cortical vBMD, cortical thickness, and cortical area, as well as more rapid increases in trabecular area compared to higher grip strength quartiles. ( 32 ) Similar to our cross‐sectional findings, this longitudinal study found that grip strength was not associated with changes in measures of trabecular microarchitecture (thickness, number, separation), though the lack of association may be attributed to the limitations of how the endocortical surface is defined in longitudinal HR‐pQCT analyses leading to an incorrect characterization of trabecularization at the endocortical surface and subsequently biased estimates of changes in trabecular indices over time. ( 32 ) While we did not observe consistent associations with vBMD in our study, and neither total cross‐sectional area nor estimated bone strength were evaluated in the STRAMBO study, our results are in line with the longitudinal findings of a positive relation between grip strength and changes in cortical bone thickness.…”
Section: Discussionsupporting
confidence: 80%
“…In a more recent investigation over 8 years of follow‐up in the STRAMBO cohort, men in the lowest quartile of baseline grip strength had accelerated declines in total vBMD, cortical vBMD, cortical thickness, and cortical area, as well as more rapid increases in trabecular area compared to higher grip strength quartiles. ( 32 ) Similar to our cross‐sectional findings, this longitudinal study found that grip strength was not associated with changes in measures of trabecular microarchitecture (thickness, number, separation), though the lack of association may be attributed to the limitations of how the endocortical surface is defined in longitudinal HR‐pQCT analyses leading to an incorrect characterization of trabecularization at the endocortical surface and subsequently biased estimates of changes in trabecular indices over time. ( 32 ) While we did not observe consistent associations with vBMD in our study, and neither total cross‐sectional area nor estimated bone strength were evaluated in the STRAMBO study, our results are in line with the longitudinal findings of a positive relation between grip strength and changes in cortical bone thickness.…”
Section: Discussionsupporting
confidence: 80%
“…Other studies showed that MAP2K5 is essential for the early stages of myogenesis [38][39][40]. As ERK5 and MAP2K5 modulate IGF-2 to regulate promyogenic activities, muscle atrophy by an impaired MAPK5/ERK5 pathway can cause impaired bone microarchitecture [39,41]. However, further studies are needed to confirm the association of rs11630730 with decreased expression of MAP2K5 in the bone or muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence supports the perception of sarcopenia and functional decline being critical factors of elevated fracture risk, commonly re ected in approaches to de ne a condition of osteosarcopenia (11,12). Current literature con rms that individuals with both conditions are at higher risk for decreased mobility, general health issues and increased mortality (8,13,14). In this context, functional decline and impaired mobility or dysmobility appear to be of particular clinical signi cance in aging men (15,16).…”
Section: Introductionmentioning
confidence: 94%